Sistem Zonasi dan Implikasinya terhadap Sustainibilitas Mutu Pendidikan di SMAN 1 Narmada - M. Amin Kutbi (LP2M STIT Palapa Nusantara, 2023)
The New Student Admission System (PPDB) is one of the efforts to provide quality education with the goals of equalizing the quality of education and involving the community in the process. The limited school capacity has become a concern as centralized school selection has led to some schools having a shortage of students. The zoning system has been adopted as a solution to address this issue, where student selection is based on proximity to the school rather than academic achievement. This research focuses on the implementation of the zoning system at SMA Negeri 1 Narmada and its implications for education quality. A qualitative approach was employed, using interviews, observations, and documentation as data collection techniques. The data were analyzed using an interactive model consisting of data reduction, data display, and verification, with increased attentiveness and triangulation to ensure data validity. The findings indicate that the zoning system has been in place at SMA Negeri 1 Narmada since its implementation. This system has had a positive impact on education quality by diversifying the accepted students. The implications are evident in both academic and non-academic aspects, as students have excelled academically and in various competitions. The school's head adopted several strategies to maintain education quality, including setting school objectives, conducting supervision and evaluation of teaching, coordinating the curriculum, and monitoring student progress. With the implementation of the zoning system, SMA Negeri 1 Narmada has successfully achieved equalization of education quality and increased student participation in various learning aspects, thus strengthening the efforts to create a sustainable and high-quality education.